Ocean color anomaly detection to estimate surface Calanus finmarchicus concentration in the Gulf of Maine - Shunmugapandi, Rebekah; McCarry, Cait L.; McKee, David; Mitchell, Catherine (Frontiers in Marine Science, 2025)
The planktonic copepod, Calanus finmarchicus, plays a pivotal role in the Gulf of Maine (GoM) pelagic food web as a primary food source for many species, including the critically endangered North Atlantic right whale (NARW). Thus, observing C. finmarchicus on a Gulf-wide scale via satellite could be beneficial for understanding changes in the migration patterns of the NARW. This study investigated the application of ocean color remote sensing to detect the surface population levels of C. finmarchicus in the GoM. Using remote sensing reflectance data from the MODIS Aqua sensor, we processed enhanced RGB (eRGB) imagery to detect and quantify the presence of C. finmarchicus, which is identifiable by its red astaxanthin pigment. This study employed a refined approach from the method originally developed off the coast of Norway, which integrates eRGB imagery and radiative transfer modeling to generate optical anomaly maps that are used for quantifying surface C. finmarchicus concentrations in the GoM. We detected surface swarms of C. finmarchicus in the ocean color imagery and estimated their concentrations. However, due to the method’s reliance on astaxanthin/red pigment-based detection, other astaxanthin-rich red/brown plankton were misidentified as C. finmarchicus. While the approach presented is effective for identifying astaxanthin anomalies in ocean color and holds potential for quantifying the surface populations of C. finmarchicus, it requires local knowledge to accurately quantify the C. finmarchicus abundances.